The effects of age on mitochondria, axonal transport, and axonal degeneration after chronic IOP elevation using a murine ocular explant model. (July 2018) - Kimball, Elizabeth C.; Jefferys, Joan L.; Pease, Mary E.; Oglesby, Ericka N.; Nguyen, Cathy; Schaub, Julie; Pitha, Ian; Quigley, Harry A.
Abstract: The purpose of this study was to compare younger and older mice after chronic intraocular pressure (IOP) elevation lasting up to 4 days with respect to mitochondrial density, structure, and movement, as well as axonal integrity, in an ex vivo explant model. We studied 2 transgenic mouse strains, both on a C57BL/6J background, one expressing yellow fluorescent protein (YFP) in selected axons and one expressing cyan fluorescent protein (CFP) in all mitochondria. Mice of 4 months or 14 months of age were exposed to chronic IOP by anterior chamber microbead injection for 14 h, 1, 3, or 4 days. The optic nerve head of globe--optic nerve explants were examined by laser scanning microscopy. Mitochondrial density, structure, and movement were quantified in the CFP explants, and axonal integrity was quantified in YFP explants. In control mice, there was a trend towards decreased mitochondrial density (# per mm2) with age when comparing younger to older, control mice, but this was not significant (1947 ± 653 vs 1412 ± 356; p = 0.19). Mitochondrial density decreased after IOP elevation, significantly, by 31%, in younger mice (p = 0.04) but trending towards a decrease, by 22%, in older mice (p = 0.82) compared to age matched controls. Mitochondrial mean size was not altered after chronic IOP elevation for 14 h or more (p ≥ 0.16). When assessing mitochondrial movement, in younger mice, 5% were mobile at any given time; 4% in the anterograde direction and 1% retrograde. In younger untreated tissue, only 75% of explants had moving mitochondria (mean = 15.8 moving/explant), while after glaucoma induction only 24% of explants had moving mitochondria (mean = 4.2 moving/explant; difference from control, p = 0.03). The distance mitochondria traveled in younger mice was unchanged after glaucoma exposure, but in older glaucoma explants the distance traveled was less than half of older controls (p < 0.0003). In younger mice, mitochondrial speed increased after 14 h of elevated IOP (p = 0.006); however, in older glaucoma explants, movement was actually slower than controls (p = 0.02). In RGC-YFP explants, axonal integrity declined significantly after 4 days of IOP elevation to a similar degree in both younger and older mice. Older mice underwent greater loss of mitochondrial movement with chronic IOP elevation than younger mice, but suffered similar short-term axonal fragmentation in C57BL/6J mice. These transgenic strains, studied in explants, permit observations of alterations in intracellular structure and organelle activity in experimental glaucoma. Highlights: Explant model of the mouse eye was used to study retinal ganglion cell axons and mitochondria changes in the optic nerve head, in both older and younger mice. Using an LSM, imaging at the ONH was possible in 2 transgenic mouse strains; 1 fluorescently expressing select RGC axons & another all mitochondria. Glaucoma caused fragmentation of axon structures at the ONH, increasing in severity with longer periods of glaucoma exposure. Comparable fragmentation of the RGCs was found between young and older glaucoma exposed mice. Glaucoma bead model caused a significant decrease in mitochondria density in both younger and older exposed mice. A significant decrease in mitochondrial movement also occurred after glaucoma bead model exposure in younger and older mice.